A Review of Performance Measurement for Successful Concurrent Construction. (14th July 2016) - Ahmad, Saad B.S.; Svalestuen, Fredrik; Andersen, Bjørn; Torp, Olav
Abstract: Concurrent engineering and performance measurement are both manufacturing industry concepts that have coexisted and complemented each other for the manufacturing industry success. Construction industry has integrated manufacturing philosophies but still waits for the success manufacturing industry enjoyed. With the help from the literature, the paper looks into the status of performance measurements in construction. The literature review generated more questions than answers. It reflected that the existing construction industry structure needs overhauling. Finally, the paper presents six questions with the help of literature evaluation for future research to start a focused debate on measuring the success of concurrent construction.